Átomos y burbujas: el atomismo del joven Leibniz en la Dissertatio y la Hipothesis physica nova y la influencia de Gassendi - Higueras Cabrera, Manuel (2014)
This article is focused on Leibniz’s early youth texts, particularly Dissertatio de arte combinatoria and Hipothesis physica nova, in order to trail in them what type of atomism the young Leibniz defended and what type of atomism rejected. At the same time, we will analyze the influence of Pierre Gassendi’s atomism.